Impact of supplementation with different protein sources on the parasitological profile of ovine matrices and development of lambs (Bioscience Journal, 2020)
The aim was to evaluate the impact of supplementation with different protein sources from agro-industrial production on the parasitological profile of ovine matrices and the development of their offspring. The protein sources used were: soybean bran, cotton pie, babassu pie, and coconut pie. A total of 60 ovine matrices were used, with confirmed pregnancy and supplemented in the final third of gestation at 0.5% of live weight in pastures of deferred Marandu grass. The evaluations occurred from the final third of gestation and in the lactation phase until weaning. The data collected in the matrices were: counting of eggs per gram of feces (EPG) and identification of infective larvae (Faecal test), evaluation of the degree of anemia by the FAMACHA©  method, body weight (kg), and body condition score (BCS). In the lambs, the biometric measurements were taken from the 30 days of life until weaning. In Faecal test, the prevalence was 98% of Haemonchus spp. There was no effect of the protein sources for EPG (3476.0) and FAMACHA©. However, in the mats supplemented with coconut pie were observed the lowest body weights (36.9 kg) and lower BCS (2.7). Babassu, coconut and cotton cakes, and soybean meal used as a protein source in the supplementation of ovine matrices kept in deferred pastures of Marandu grass at the 0.5% level of live weight maintain the production indexes consistent with the physiology stage of the matrices even with a high endo-parasitic load.